SEJARAH PERKEMBANGAN YAYASAN DAN PONDOK PESANTREN DARUSSALAM SURABAYA 1981-2017 - Lailil Masruroh (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2018)
Abstract: This article discusses the history and development of the foundation and the Darussalam Islamic boarding school in Surabaya. This article limits the problem to three things, namely (1) the history of the establishment of the Darussalam Tambak Madu Simokerto Islamic Boarding School and Foundation, Surabaya (2) the development of the Tambak Madu Simokerto Islamic Boarding School and Foundation and Islamic Boarding School in 1981-2017 (3) supporting and inhibiting factors for the Foundation and Islamic Boarding School Simokerto Honey Pond. This study uses a historical approach with a diachronic perspective and a sociological approach. While the sociological approach is useful as a tool to support the social aspects of the events studied, which include developments, the influence of figures and the surrounding community. The theory used is the theory of Continuity and Change by John Obert Voll which aims to explain the various changes experienced by foundations on an ongoing basis. While the method uses the historical method through the steps of data collection, source criticism, interpretation and historiography. This article concludes that (1) Initially this foundation was in the form of a prayer room which was used for recitation activities by Kiai Noer Ahmad. This foundation was established in 1981, and following the establishment of Pondok Darussalam in 1983. (2) The development of the Darussalam Foundation and Islamic Boarding School was divided into three periods, and now has three formal and non-formal educational institutions. (3) Supporting and inhibiting factors for the development of foundations are quite religious. Keywords: history, development, foundation, pesantren